2021
DOI: 10.1186/s12866-021-02326-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in the pathogenic foodborne bacteria isolated from raw kebab and hamburger: phenotypic and genotypic study

Abstract: Background In recent years, interest in the consumption of ready-to-eat (RTE) food products has been increased in many countries. However, RTE products particularly those prepared by meat may be potential vehicles of antibiotic-resistance foodborne pathogens. Considering kebab and hamburger are the most popular RTE meat products in Iran, this study aimed to investigate the prevalence and antimicrobial resistance of common foodborne pathogens (Escherichia coli, Salmonella spp., Staphylococcus au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 87 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…Among them, 15 (48.4%) gave positive amplicons for bla TEM , while 5 (20.8%) isolates exhibited the temB gene, and none of the temA genes were found. Similar to our findings, high rates of bla TEM (44.11%) were found by Rajaei et al [ 53 ] in Salmonella spp. isolates from raw kebab and hamburger in Iran and by Moawad et al [ 54 ] in Egypt (73.3%) in Salmonella spp.…”
Section: Resultssupporting
confidence: 93%
“…Among them, 15 (48.4%) gave positive amplicons for bla TEM , while 5 (20.8%) isolates exhibited the temB gene, and none of the temA genes were found. Similar to our findings, high rates of bla TEM (44.11%) were found by Rajaei et al [ 53 ] in Salmonella spp. isolates from raw kebab and hamburger in Iran and by Moawad et al [ 54 ] in Egypt (73.3%) in Salmonella spp.…”
Section: Resultssupporting
confidence: 93%
“…The existence of antimicrobial-resistant bacteria in food may lead to difficulty treating foodborne infections in humans. Their presence in food can also facilitate the transfer of resistant genes to other microorganisms through the food chain [ 36 , 37 , 38 ]. In our study, the phenotypic resistance observed against streptomycin, sulfamethoxazole, trimethoprim, cefotetan, oxytetracyclines vancomycin, and ceftriaxone was similar to previous reports on antibiotic resistance of L. monocytogenes from food tested against several antimicrobials [ 34 , 35 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The slaughtering process represents a possible point of bacterial contamination; for this reason, methods of prevention, disinfection, and control must be followed to reduce the risk of meat contamination by pathogenic species [2,3]. The presence of antibiotic-resistant (AR) strains increases the level of risk related to their presence in meat [4,5]. This is linked to a risk to human health due to antibiotic ineffectiveness and possible transmission of genes related to antibiotic resistance between bacteria [6].…”
Section: Introductionmentioning
confidence: 99%